An easy construction of generalized neighbor designs in minimal circular blocks: DOI: 10.48129/kjs.13715 - Muhammad Nadeem; Muhammad Rasheed; M. H. Tahir; Khadija Noreen; Sajid Hussain; Rashid Ahmed (Kuwait Journal of Science, 2022)
Neighbor designs are used in the experiments where neighbor effects may arise. Neighbor designs neutralize these effects, therefore, considered to be robust to neighbor effects. Minimal neighbor designs are always economical among the neighbor designs, therefore, preferred by the experimenters. Method of cyclic shifts provides the construction of these designs in circular blocks only for odd v (number of treatments). For v even, minimal circular generalized neighbor designsin which only v/2 unordered pairs of distinct treatments do not appear as neighbors will be the better alternate to the minimal neighbor designs. In this article, such minimal generalized neighbor designs are constructed in circular blocks for v even.